Buccally impacted maxillary canines increase the likelihood of root separation in adjacent first premolars. (13th September 2016) - Cao, D; Zhu, L; Chen, Y; Xie, L; Yan, B; Sun, Z
Abstract : Objective: To investigate the influence of maxillary impacted canines on the root morphology of adjacent premolars in a Chinese population. Subjects and Methods: A sample of 370 Chinese subjects with maxillary canine impaction and 370 control subjects were collected in this study. CBCT data of all subjects were collected and analyzed. The prevalence of separate‐rooted maxillary premolars was compared between subjects with and without impacted canines. Then, the prevalence of separate‐rooted maxillary premolars was compared between subjects with buccal canine impaction (BIC) and those with palatal impaction (PIC). Results: The prevalence of separate‐rooted first premolars was significantly higher in the canine impaction group ( P = 0.046), but the prevalence of separate‐rooted second premolars was not different ( P = 0.780). Furthermore, a significant higher prevalence of first premolar root separation was found on the impacted site in the BIC subgroup ( P < 0.001), but not in the PIC subgroup ( P = 0.508). Also, the prevalence of separate‐rooted first premolars in the BIC subgroup was significantly higher than that of the control group ( P = 0.008), but not so for the PIC subgroup ( P = 0.097). Conclusions: Buccally impacted maxillary canines are associated with an increased prevalence of root separation in the adjacent maxillary first premolars. This is likely because that buccally impacted canines encroach on the space needed for root development of the first premolars.